The effectiveness of the Class of Pregnant Women and the Class of Pregnant Women plus Psychoeducation in Reducing Cortisol levels and Stress levels of Pregnant Women: A Systematic Review - Pida, Paulina; Runjati, Runjati; Suhartono, Suhartono (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Pregnancy puts a mother in a condition that is prone to stress due to physical and psychological changes. Mothers with high stress levels are at risk of experiencing complications to the mother and baby during pregnancy, childbirth and the puerperium. To analyze the effect of the class of pregnant women and the class of pregnant women plus psychoeducation on cortisol levels and stress levels of pregnant women using a systematic review method. This type of research is a systematic review with the method used is PRISMA. The literature studied ranged from 2015 to 2020. KIH can reduce stress levels and cortisol levels of pregnant women. The search results obtained 25 research articles.The results showed that KIH plus psychoeducation can reduce stress levels and cortisol levels and improve psychosocial well-being compared to standard KIH and antenatal care.